2021
DOI: 10.23887/ijee.v5i1.33151
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of The Flipped Classroom for Early Grade Students in Elementary School

Abstract: The educational paradigm in the 21st-century coronavirus pandemic requires a deeper research study. This study aims to improve the mathematics learning outcomes of grade 1 students using the flipped classroom model and to find out their responses to the use of this model. The subjects of this study were 7 students who were grade 1 student. The research design used classroom action research consisting of planning, implementing, observing, and reflecting. Data were analyzed descriptively with qualitative and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
5
0
2
Order By: Relevance
“…The findings of this study are in line with the results of several studies that have been conducted by previous researchers such as research (Hidayah & Mustadi, 2021), in their research in elementary school regarding mathematics subjects, found that students who studied with the flipped classroom strategy showed increased learning achievement because this strategy made it easy to learn mathematics material, increased selfconfidence, and were active and free to choose a learning style.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study are in line with the results of several studies that have been conducted by previous researchers such as research (Hidayah & Mustadi, 2021), in their research in elementary school regarding mathematics subjects, found that students who studied with the flipped classroom strategy showed increased learning achievement because this strategy made it easy to learn mathematics material, increased selfconfidence, and were active and free to choose a learning style.…”
Section: Discussionsupporting
confidence: 91%
“…Contohnya penggunaan teknologi 4G dan jalur lebar menjadi medium arus perdana bagi meneruskan sesi persekolahan dalam usaha memutuskan rantaian jangkitan COVID-19. Perubahan drastik ini telah mengesa para guru untuk mengubah kaedah penyampaian agar proses pembelajaran dan pembinaan kemahiran mereka dalam pembelajaran matematik dapat diteruskan (Hidayah & Mustadi, 2021). Dalam konteks pembelajaran matematik, interaksi dua hala guru-murid diperlukan bagi membentuk kefahaman jelas terhadap konsep dan teori matematik yang bersifat abstrak.…”
Section: Pengenalanunclassified
“…(Dewi, Manuaba and Ganesha, 2018) The result of interaction with the environment is knowledge that will be built by the child at the end of the learning process. (Hidayah and Mustadi, 2021) These cognitive conflicts can achieve balance through changes in cognitive structures (schemata) that occur during the interaction process between the initial conception and new phenomena that can be integrated. These events will occur continuously as long as students receive new knowledge.…”
Section: Learning Cycle Management In Instilling Religious Charactermentioning
confidence: 99%